Analisis Interaksi Cross Equatorial-Northerly Surge Dan Southerly Surge Pada Periode Madden-Julian Oscillation Terhadap Dinamika Atmosfer Pada Saat Musim Dingin Boreal Di Pulau Jawa - Ihza Carundyatama, Daniar; Safri Emanuel Manullang; Yoseph Darrel Krisnawan; Krisna Dwi Oktabrian (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
A surge is an atmospheric dynamic event characterised by the intrusion of stronger-than-normal winds, bringing air from high latitudes to low latitudes. There are two surges that cross the Indonesian equator: the Cross Equatorial Northerly Surge (CENS) and the Southerly Surge (SS). This study examines the influence of the interaction between CENS, SS, and the Madden-Julian Oscillation (MJO) on atmospheric dynamics in Java during the 2014–2023 boreal winter season. This study provides insights into how global and mesoscale atmospheric phenomena influence weather patterns in the western Maritime Continent, especially on the island of Java. The CENS and SS indices were identified using meridional wind data, while the MJO index was calculated based on the RMM amplitude. Rainfall, Outgoing Longwave Radiation (OLR), and moisture transport data were analyzed using Climate Data Operator (CDO) software and bootstrap significance testing. The results indicate that active MJO significantly enhances rainfall over Java Island during interactions with CENS, while interactions with SS predominantly affect the eastern part of the island. When MJO is inactive, the impact patterns of CENS and SS on local atmospheric dynamics vary. Negative OLR anomalies and increased moisture transport highlight MJO's role in amplifying convective activity. The interaction between CENS, SS, and MJO has increased atmospheric instability in several areas of Java. SS has contributed to a reduction in rainfall in parts of Java.